Composite drug-loaded nano particle based on calcium peroxide carrier and preparation method of composite drug-loaded nano particle
By loading polylysine-dihydrobenzene e6 onto hyaluronic acid-modified calcium peroxide nanoparticles, CaO2@HA/pllCe6 nanoparticles are formed, which solves the problem of traditional antibiotic treatment ineffective against drug-resistant bacteria and poor photodynamic therapy in an hypoxic environment, and achieves the effect of enhancing photodynamic therapy and alleviating biofilm hypoxia.
Patent Information
- Application Number
- CN202411879461.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Traditional antibiotic treatments are ineffective against drug-resistant bacteria, and photodynamic therapy is not effective in the microenvironment of hypoxic bacteria. A new method that enhances photodynamic therapy and relieves biofilm hypoxia is needed.
Using compound drug-loaded nanoparticles based on calcium peroxide carrier, polylysine-dihydroprophene e6 (pllCe6) is loaded onto the surface of hyaluronic acid-modified calcium peroxide nanoparticles to form CaO2@HA/pllCe6 nanoparticles to enhance the oxygen concentration at the bacterial infection site.
The efficiency of photodynamic therapy is improved, and the hypoxia problem is alleviated by releasing H2O2 and O2 in bacterial biofilms is significantly improved.
Smart Images

Figure CN119656132A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medicine preparation, and in particular to composite drug-carrying nanoparticles based on a calcium peroxide carrier and a preparation method thereof. Background Art
[0002] Staphylococcus aureus is a major human pathogen that possesses a range of virulence factors and is resistant to most antibiotics. Biofilm is a bacterial aggregate membrane formed by bacteria wrapping themselves and aggregating in an extracellular polymer matrix (EPS) to resist harsh environmental conditions. EPS accounts for up to 80% of the biofilm, which protects the internal bacteria from external toxic substances, thus creating a strong natural barrier for effective antimicrobial drugs and evading the host cell's immune system. The formation of MRSA biofilm further exacerbates the severity of MRSA infection and exhibits stubborn drug resistance and tolerance.
[0003] Traditional antibiotic treatment can induce severe bacterial resistance, further challenging the availability of existing drugs and treatment options. Therefore, it is crucial to develop new strategies to effectively eradicate resistant bacteria. In recent years, photodynamic therapy has become an effective way to treat microbial infections. The principle is that laser irradiation of photosensitizers reaches an excited state. Under the interaction of the internal system, the energy released by the excited state photosensitizer converts oxygen into lethal reactive oxygen free radicals. However, in an oxygen-deficient bacterial microenvironment, the photodynamic effect may aggravate the hypoxia of the bacterial microenvironment and even promote bacterial growth. Therefore, timely supplementation of oxygen is the key to enhancing photodynamic killing and improving the bacterial hypoxic microenvironment. Summary of the invention
[0004] Based on the above technical problems, the present invention aims to provide a composite drug-loaded nanoparticle based on calcium peroxide carrier for enhancing photodynamic therapy and alleviating biofilm hypoxia. pll Ce6) loaded with hyaluronic acid-modified calcium peroxide nanoparticles to enhance the photodynamic efficacy of oxygen-dependent photosensitizers by increasing the oxygen concentration at the bacterial infection site.
[0005] Another object of the present invention is to provide a method for preparing the composite drug-loaded nanoparticles based on calcium peroxide carrier. The method effectively solves the problem that during the loading process of the active ingredient dihydrochlorin e6, it is difficult to load it onto the surface of calcium peroxide and it is impossible to form a nanocomposite material that uniformly loads the active ingredient, thereby effectively improving the catalytic activity of Ce6 and improving the therapeutic effect.
[0006] The purpose of the present invention is achieved through the following technical solutions: A composite drug-loaded nanoparticle based on a calcium peroxide carrier, characterized in that: calcium peroxide nanoparticles modified with hyaluronic acid are used as carriers, and poly-lysine-dihydrochlorin e6 ( pll Composite drug-loaded nanoparticles CaO2@HA / pll Ce6, the composite drug-loaded nanoparticles are spherical particles with a particle size of about 100nm.
[0007] Further, the poly-lysine-dihydrochlorin e6 ( pll Ce6) is a cationic photosensitizer with strong electrostatic adsorption ability.
[0008] A method for preparing composite drug-carrying nanoparticles based on calcium peroxide carriers, comprising the preparation of hyaluronic acid-modified calcium peroxide nanocarriers and the compounding of medicinal ingredients, characterized in that: the compounding of the effective ingredients is to combine the effective ingredient polylysine-dihydrochlorin e6 ( pll Ce6) solution was added dropwise to the suspension of hyaluronic acid-modified calcium peroxide nanomaterials, and the solution was placed on a rotary suspension instrument for 10 min and centrifuged to obtain the loaded pll Ce6 hyaluronic acid modified calcium peroxide nanoparticles CaO2@HA / pll Ce6.
[0009] Further, the pll The concentration of Ce6 solution was 1 mg / mL, and the concentration of suspension of hyaluronic acid-modified calcium peroxide nanomaterials was 1 mg / mL.
[0010] The composite particles of Ce6 and calcium peroxide nanoparticles with self-oxygenation can solve the problem of hypoxia during the photodynamic effect of Ce6. However, in the process of attaching Ce6 to the surface of calcium peroxide nanoparticles with oxygen supply, it is found that Ce6 is basically unable to attach to the surface of calcium peroxide nanoparticles. In the present invention, Ce6 is modified by polylysine to convert it into pll Ce6, and then compounded with hyaluronic acid modified calcium peroxide nanoparticles. Sodium hyaluronate effectively modifies calcium peroxide nanoparticles during nucleation and growth through the attraction between negatively charged ions and positively charged calcium peroxide nanocrystals to form CaO2@HA. CaO2@HA6 is then compounded with hyaluronic acid modified calcium peroxide nanoparticles. pll Electrostatic interaction is generated between Ce, making pll Ce6 is uniformly attached to the surface of CaO2@HA, forming CaO2@HA / pll Ce6.
[0011] Further, the pll The volume ratio of Ce6 solution and hyaluronic acid-modified calcium peroxide nanomaterial suspension is 1:1~1.5.
[0012] Furthermore, poly-lysine-dihydrochlorin e6 ( pll The synthesis steps of Ce6 are as follows: (1) Synthesis of N-hydroxysuccinimide ester Ce6 (Ce6-NHS): N-hydroxysuccinimide ester (NHS), N,N'-dicyclohexylcarbodiimide (DCC) and Ce6 were dissolved in dry DMSO solution and reacted at room temperature in the dark for 24 h to obtain Ce6-NHS; (2) pll Synthesis of Ce6: N-ethylmorpholine (NEM), polylysine (pll) and Ce6-NHS were dissolved in DMSO, reacted at room temperature in the dark for 24 h, and then dialyzed and freeze-dried to obtain the product. pll Ce6.
[0013] Furthermore, the dosage ratio of NHS, DCC, Ce6 and DMSO is 2~3mg:2~3mg:1mg:10mL.
[0014] Furthermore, the dosage ratio of NEM, pll, Ce6-NHS and DMSO is 0.8~1.2 mg:0.8~1.2 mg:5~7 mg:10 mL.
[0015] Furthermore, the hyaluronic acid modified calcium peroxide nanocomposite material is prepared according to the following steps: (1) Weigh sodium hyaluronate and hyaluronic acid, add them into deionized water, and sonicate to fully dissolve them to obtain solution 1; (2) Adding calcium chloride aqueous solution to solution 1, and rapidly stirring at room temperature to obtain solution 2; (3) Adding sodium hydroxide aqueous solution to solution 2 and mixing thoroughly to obtain solution 3; (4) adding hydrogen peroxide solution dropwise to solution 3 and continuing rapid stirring at room temperature to obtain solution 4; (5) The milky blue solution 4 was centrifuged at 12000 rpm for 10 min to separate the solid product. After washing, the product was re-dispersed with deionized water to prepare a suspension of hyaluronic acid-modified calcium peroxide nanocomposite material with a concentration of 1 mg / mL.
[0016] Furthermore, the dosage ratio of the sodium hyaluronate, hyaluronic acid and deionized water is 15-20 mg: 3-5 mg: 4-5 mL.
[0017] Furthermore, the volume ratio of the solution 1 to the sodium hydroxide aqueous solution is 2:0.8-1.2, and the concentration of the calcium chloride aqueous solution is 0.05-0.15 mol / L.
[0018] Furthermore, the volume ratio of the solution 2 to the sodium hydroxide aqueous solution is 3:1.5-2.5, and the concentration of the sodium hydroxide aqueous solution is 2-3 mol / L.
[0019] Furthermore, the volume ratio of the solution 3 to the hydrogen peroxide solution is 12-13 mL: 240-250 μL, and the mass volume concentration of the hydrogen peroxide solution is 30%.
[0020] Most specifically, a method for preparing composite drug-loaded nanoparticles based on a calcium peroxide carrier is characterized by comprising the following steps: S1. Preparation of hyaluronic acid-modified calcium peroxide nanomaterials (1) Weigh sodium hyaluronate and hyaluronic acid, add them to deionized water, and sonicate them to fully dissolve them to obtain solution 1, wherein the amount ratio of sodium hyaluronate, hyaluronic acid and deionized water is 15-20 mg: 3-5 mg: 4-5 mL; (2) adding a calcium chloride aqueous solution to solution 1, and rapidly stirring and mixing at room temperature to obtain solution 2, wherein the volume ratio of solution 1 to the sodium hydroxide aqueous solution is 2:0.8-1.2, and the concentration of the calcium chloride aqueous solution is 0.05-0.15 mol / L; (3) adding sodium hydroxide aqueous solution to solution 2 and thoroughly mixing solution 3, wherein the volume ratio of solution 2 to the sodium hydroxide aqueous solution is 3:1.5-2.5, and the concentration of the sodium hydroxide aqueous solution is 2-3 mol / L; (4) adding hydrogen peroxide solution dropwise to solution 3, and continuing rapid stirring at room temperature to obtain solution 4, wherein the volume ratio of solution 3 to hydrogen peroxide solution is 12-13 mL: 240-250 μL, and the mass volume concentration of hydrogen peroxide solution is 30%; (5) Centrifuging the milky blue solution 4 at 12000 rpm for 10 min to separate the solid product, and after washing, re-dispersing the product with deionized water to prepare a suspension of hyaluronic acid-modified calcium peroxide nanocomposite material with a concentration of 1 mg / mL; S2. Compounding of active ingredients (1) pll Preparation of Ce6: N-hydroxysuccinimide ester (NHS), N,N'-dicyclohexylcarbodiimide (DCC) and Ce6 were dissolved in a dry DMSO solution, and reacted at room temperature in the dark for 24 h to obtain Ce6-NHS, wherein the dosage ratio of NHS, DCC, Ce6 and DMSO was 2~3 mg:2~3 mg:1 mg:10 mL; N-ethylmorpholine (NEM), pll and Ce6-NHS were dissolved in dry DMSO, and reacted at room temperature in the dark for 24 h, and then dialyzed and freeze-dried to obtain the product. pllCe6, the dosage ratio of NEM, pll, Ce6-NHS and DMSO is 0.8~1.2mg:0.8~1.2mg:5~7mg:10mL; (2) pll Ce6 was prepared into 1 mg / mL pll Ce6 solution was added dropwise to a suspension of 1 mg / mL hyaluronic acid-modified calcium peroxide nanocomposite to obtain a mixed solution, which was then placed on a rotary suspension instrument for 10 min. pll The volume ratio of Ce6 solution and suspension is 1:1~1.5; (3) The mixed solution was centrifuged at 12000 rpm for 10 min to separate the loaded pll Ce6 hyaluronic acid modified calcium peroxide nanoparticles.
[0021] Due to the EPR effect, CaO2@HA / pll Ce6 can accumulate at the site of infection. pll Ce6 has a weak positive charge on its surface, which can effectively penetrate into the biofilm. After initial penetration, a large amount of H2O2 is rapidly released in the weakly acidic and hyaluronidase (HAD) overexpressed bacterial biofilm microenvironment. The released H2O2 generates O2 under the catalysis of catalase, thereby alleviating biofilm hypoxia and enhancing pll On the other hand, it consumes overexpressed GSH (glutathione) through redox reaction, further improving the therapeutic efficiency of ROS.
[0022] The present invention has the following technical effects: In the present invention, Ce6 is converted into pll Ce6, then combined with hyaluronic acid-modified calcium peroxide nanoparticles, pll Ce6 is uniformly loaded on its surface to form self-oxygenating composite nano drug-carrying particles CaO2@HA / pll Ce6 solves the problem that Ce6 cannot adhere to the surface of CaO2 nanoparticles. The prepared nanocomposite particles have uniform particle size and high specific surface area. pll After Ce6 is compounded with CaO2@HA, it acts as a good bacterial microenvironment response material, which can improve the hypoxia in the bacterial area and enhance photodynamic therapy; on the other hand, it improves the biocompatibility and delivery efficiency of Ce6, thereby achieving significant bactericidal effects at low doses. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : In the present invention, CaO2@HA / pll Flow chart of Ce6 synthesis and application.
[0024] Figure 2 : Transmission electron microscope-element scanning image of CaO2@HA nanoparticles prepared by the present invention.
[0025] Figure 3 :CaO2@HA / pll Transmission electron microscopy image of Ce6.
[0026] Figure 4 :CaO2@HA / pll Hydration particle size diagram of Ce6.
[0027] Figure 5 : UV-visible absorption spectra of different nanoparticles.
[0028] Figure 6 : Curves of oxygen release from different nanoparticles over time.
[0029] Figure 7 : H2O2 production curves of different nanoparticles.
[0030] Figure 8 : GSH consumption curves of different nanoparticles.
[0031] Fig. 9 : Singlet oxygen generation curves of different nanoparticles.
[0032] Fig.10 :Results of in vitro bacterial affinity test of different photodynamic reagents.
[0033] Fig.11 :Results of different photodynamic agents penetrating biofilms in vitro.
[0034] Fig.12 : Comparison of the in vitro bactericidal effects of different nanoparticles.
[0035] Fig.13 :Comparison of different photodynamic agents in clearing biofilm in vitro. DETAILED DESCRIPTION
[0036] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.
[0037] Example 1 A method for preparing a self-oxygen-supplying photodynamic nanocomposite material comprises the following steps: S1. Preparation of hyaluronic acid-modified calcium peroxide nanomaterials (1) Weigh sodium hyaluronate and hyaluronic acid, add them to deionized water, and sonicate them to fully dissolve them to obtain solution 1, wherein the amount ratio of sodium hyaluronate, hyaluronic acid and deionized water is 20 mg:5 mg:5 mL; (2) adding a calcium chloride aqueous solution to solution 1, and rapidly stirring and mixing at room temperature to obtain solution 2, wherein the volume ratio of solution 1 to the sodium hydroxide aqueous solution is 2:1, and the concentration of the calcium chloride aqueous solution is 0.1 mol / L; (3) adding sodium hydroxide aqueous solution to solution 2 and thoroughly mixing solution 3, wherein the volume ratio of solution 2 to the sodium hydroxide aqueous solution is 3:2, and the concentration of the sodium hydroxide aqueous solution is 2.5 mol / L; (4) adding hydrogen peroxide solution dropwise to solution 3, and continuing rapid stirring at room temperature to obtain solution 4, wherein the volume ratio of solution 3 to hydrogen peroxide solution is 12.5 mL:240 μL, and the mass volume concentration of hydrogen peroxide solution is 30%; (5) Centrifuging the milky blue solution 4 at 12000 rpm for 10 min to separate the solid product, and after washing, re-dispersing the product with deionized water to prepare a suspension of hyaluronic acid-modified calcium peroxide nanocomposite material with a concentration of 1 mg / mL; S2. Photosensitizer compounding (1) pll Preparation of Ce6: N-hydroxysuccinimide ester (NHS), N,N'-dicyclohexylcarbodiimide (DCC) and Ce6 were dissolved in dry DMSO solution, and reacted at room temperature in the dark for 24 h to obtain Ce6-NHS, wherein the dosage ratio of NHS, DCC, Ce6 and DMSO was 2 mg:2 mg:1 mg:10 mL; N-ethylmorpholine (NEM), pll and Ce6-NHS were dissolved in dry DMSO, and reacted at room temperature in the dark for 24 h, and then dialyzed and freeze-dried to obtain the product. pll Ce6, the dosage ratio of NEM, pll, Ce6-NHS and DMSO is 1 mg:1 mg:6 mg:10 mL; (2) Add 700 μL of 1 mg / mL pll The Ce6 solution was added dropwise to 700 μL of 1 mg / mL suspension of hyaluronic acid-modified calcium peroxide nanocomposite to obtain a mixed solution, which was placed on a rotary suspension instrument for 10 min; (3) The mixed solution was centrifuged at 12000 rpm for 10 min to separate the loaded pll Ce6 hyaluronic acid modified calcium peroxide nanoparticles.
[0038] About Synthetic pllCe6, determine its maximum absorption wavelength by full wavelength scanning, measure the absorbance value at 400 nm, and calculate the degree of substitution of Ce6 on the pll chain. After calculation, the degree of substitution of Ce6 on the pll chain is 6.
[0039] The greater the degree of substitution, the smaller the positive charge will be, but the ability to generate ROS will be stronger; conversely, the smaller the degree of substitution, the stronger the positive charge will be, but the ability to generate ROS will be weakened.
[0040] The surface of hyaluronic acid-modified calcium peroxide (CaO2@HA) was negatively charged, with a zeta potential of -23.4 mV. pll The surface of Ce6 is positively charged, with a zeta potential of +30.5 mV. The CaO2@HA / pll Ce6 has a zeta potential of +1.2 mV and a weakly positive surface, which allows it to penetrate into biofilms efficiently. After initial penetration, a large amount of H2O2 is rapidly released in the weakly acidic and hyaluronidase (HAD) overexpressed bacterial biofilm microenvironment.
[0041] About the photosensitizer load test: (1) During the loading process, Ce6 was directly loaded. The zeta potential of CaO2@HA remained unchanged before and after loading, that is, the loading of Ce6 failed. The presumed reason is that Ce6 is electrically neutral and cannot be adsorbed onto the CaO2@HA surface.
[0042] (2) We also tried to use cationic polyarginine to modify Ce6. Since the zeta potential of polyarginine-modified Ce6 is +13 mV, its electrostatic adsorption performance does not match that of CaO2@HA, resulting in a low loading rate, which is completely unable to meet the requirements of later applications. In addition, the surface of the loaded nanocomposite material is obviously negatively charged, which is not conducive to its penetration into the biomembrane and has a significant inhibitory effect on its effectiveness.
[0043] Figure 2 This is the EDS image of the self-oxygen photodynamic nanocomposite material. It can be seen that the prepared CaO2@HA contains N element, which comes from hyaluronic acid, Ca element comes from calcium peroxide, and O element comes from hyaluronic acid and calcium peroxide, proving that the synthesis of CaO2@HA is successful.
[0044] Figure 3 This is a transmission electron microscope image of the self-oxygen-supplying photodynamic nanocomposite material prepared in this example. It can be seen that the prepared nanoparticles have regular morphology and uniform size, and are spherical nanoparticles with a particle size of about 100 nm.
[0045] Figure 4 The hydrated particle size diagram of the self-oxygen photodynamic nanocomposite material shows that CaO2@HA / pllThe average particle size of Ce6 is 138 nm and is evenly dispersed.
[0046] Figure 5 The UV-visible absorption spectra of each nanoparticle show that CaO2@HA has no characteristic absorption peak at 400-800 nm. pll Ce6 has a characteristic absorption peak at 663 nm, CaO2@HA / pll Ce6 has a characteristic absorption peak at 663 nm. pll Ce6 was successfully adsorbed on the CaO2@HA surface.
[0047] Figure 6 The oxygen release results of each nanoparticle under the same conditions show that the free Ce6 and pll Ce6 does not contribute to the release of oxygen, while CaO2@HA and CaO2@HA / pll Ce6 obviously released oxygen, and the oxygen release efficiency was basically the same in the early stage. After 120 minutes, pll The oxygen release rate corresponding to Ce6 / CaO2@HA is significantly higher than that of CaO2@HA, i.e. pll The loading of Ce6 on the surface of CaO2@HA significantly improved the oxygen release efficiency of the nanocomposite.
[0048] Figure 7 The results of H2O2 production of each nanoparticle under different light drive are shown in Figure 2. It can be seen that the free Ce6 and pll Ce6 has no effect on H2O2 production, while in the range of 300-550nm, CaO2@HA and CaO2@HA / pll Ce6 significantly promoted the production of H2O2.
[0049] Figure 8 The GSH consumption curves of the nanoparticles under different light wavelengths show that CaO2@HA2 and CaO2@HA / pll Ce6 significantly increased the consumption of GSH.
[0050] Singlet oxygen is a special state of molecular oxygen, often called reactive oxygen, which is the excited state of ordinary oxygen (O2). Oxygen molecules in this state have high reactivity. The effects of different nanoparticles on singlet oxygen production were tested in the presence of glutathione (GSH). The results are as follows: Fig. 9 As shown in the figure, it can be seen that under the same light wavelength conditions, pll Compared with free Ce6, Ce6 produces more singlet oxygen. CaO2@HA alone contributes less to the production of singlet oxygen because the H2O2 produced under GSH conditions is largely consumed.pll After Ce6 was loaded onto the CaO2@HA surface, the generation of singlet oxygen was further increased, which indicates that pll After Ce6 is loaded onto CaO2@HA, a synergistic effect is produced between the two. Hyaluronic acid-modified calcium peroxide can activate the catalytic activity of Ce6's photosensitizer, and the photosensitizer produces more singlet oxygen, thereby increasing photodynamic force.
[0051] Fig.10 The results of in vitro bacterial affinity tests of different nanoparticle reagents are shown in Figure 2. pll Ce6 and CaO2@HA / pll Ce6 can be effectively adsorbed on the bacterial surface, while free Ce6 cannot be adsorbed on the bacterial surface. This is related to the positive charge pll This is related to the stronger bacterial affinity of Ce6.
[0052] Fig.11 The results of in vitro biofilm penetration of various nanoparticle reagents are shown in Figure 2. pll Ce6 and CaO2@HA / pll Ce6 can effectively penetrate bacterial biofilms, but free Ce6 cannot.
[0053] Fig.12 The results of in vitro sterilization of various nanoparticle reagents are shown. pll Ce6 can effectively kill MRSA planktonic bacteria, and the bacterial morphology of MRSA planktonic bacteria changes significantly. CaO2@HA / pll Ce6 can effectively release H2O2, and the released H2O2 can directly react with GSH to generate O2, thereby improving the photodynamic bactericidal ability.
[0054] Fig.13 The results of nanoparticle reagents removing biofilm in vitro. It can be seen that CaO2@HA / pll Ce6 can effectively remove bacterial biofilm, CaO2@HA / pll Ce6 can effectively penetrate bacterial biofilms and release H2O2, enhancing photodynamic bactericidal performance.
[0055] Example 2 A method for preparing a self-oxygen-supplying photodynamic nanocomposite material comprises the following steps: S1. Preparation of hyaluronic acid-modified calcium peroxide nanomaterials (1) Weigh sodium hyaluronate and hyaluronic acid, add them to deionized water, and sonicate them to fully dissolve them to obtain solution 1, wherein the amount ratio of sodium hyaluronate, hyaluronic acid and deionized water is 15 mg:3 mg:4 mL; (2) adding a calcium chloride aqueous solution to solution 1, and rapidly stirring and mixing at room temperature to obtain solution 2, wherein the volume ratio of solution 1 to the sodium hydroxide aqueous solution is 2:0.8, and the concentration of the calcium chloride aqueous solution is 0.15 mol / L; (3) adding sodium hydroxide aqueous solution to solution 2 and thoroughly mixing solution 3, wherein the volume ratio of solution 2 to the sodium hydroxide aqueous solution is 3:1.5, and the concentration of the sodium hydroxide aqueous solution is 3 mol / L; (4) adding hydrogen peroxide solution dropwise to solution 3, and continuing rapid stirring at room temperature to obtain solution 4, wherein the volume ratio of solution 3 to hydrogen peroxide solution is 13 mL:250 μL, and the mass volume concentration of hydrogen peroxide solution is 30%; (5) Centrifuging the milky blue solution 4 at 12000 rpm for 10 min to separate the solid product, and after washing, re-dispersing the product with deionized water to prepare a suspension of hyaluronic acid-modified calcium peroxide nanocomposite material with a concentration of 1 mg / mL; S2. Photosensitizer compounding (1) pll Preparation of Ce6: N-hydroxysuccinimide ester (NHS), N,N'-dicyclohexylcarbodiimide (DCC) and Ce6 were dissolved in a dry DMSO solution, and reacted at room temperature in the dark for 24 h to obtain Ce6-NHS, wherein the dosage ratio of NHS, DCC, Ce6 and DMSO was 2.5 mg:2.5 mg:1 mg:10 mL; N-ethylmorpholine (NEM), pll and Ce6-NHS were dissolved in dry DMSO, and reacted at room temperature in the dark for 24 h, and then dialyzed and freeze-dried to obtain the product. pll Ce6, the dosage ratio of NEM, pll, Ce6-NHS and DMSO is 0.8 mg:0.8 mg:5 mg:10 mL; (2) Add 1000 μL of 1 mg / mL pll Ce6 was added dropwise to 1500 μL of a suspension of hyaluronic acid-modified calcium peroxide nanocomposite material with a concentration of 1 mg / mL to obtain a mixed solution, which was placed on a rotary suspension instrument for 10 min; (3) The mixed solution was centrifuged at 12000 rpm for 10 min to separate the loaded pll Ce6 hyaluronic acid modified calcium peroxide nanoparticles.
[0056] Calculated pll In Ce6, the substitution degree of Ce6 on the pll chain is 5. After testing, the CaO2@HA / pllCe6 zeta potential is +0.7mV, and the surface is weakly positively charged, which can effectively penetrate into the biofilm. After initial penetration, a large amount of H2O2 is rapidly released in the weakly acidic and hyaluronidase (HAD) overexpressed bacterial biofilm microenvironment. CaO2@HA / pll The average particle size of Ce6 is 135nm and it is evenly dispersed.
[0057] Example 3 A method for preparing a self-oxygen-supplying photodynamic nanocomposite material comprises the following steps: S1. Preparation of hyaluronic acid-modified calcium peroxide nanomaterials (1) Weigh sodium hyaluronate and hyaluronic acid, add them to deionized water, and sonicate to fully dissolve them to obtain solution 1, wherein the amount ratio of sodium hyaluronate, hyaluronic acid and deionized water is 18 mg:4 mg:4.5 mL; (2) adding a calcium chloride aqueous solution to solution 1, and rapidly stirring and mixing at room temperature to obtain solution 2, wherein the volume ratio of solution 1 to the sodium hydroxide aqueous solution is 2:1.2, and the concentration of the calcium chloride aqueous solution is 0.05 mol / L; (3) adding sodium hydroxide aqueous solution to solution 2 to obtain solution 3 which is thoroughly mixed, wherein the volume ratio of solution 2 to the sodium hydroxide aqueous solution is 3:2.5, and the concentration of the sodium hydroxide aqueous solution is 2 mol / L; (4) adding hydrogen peroxide solution dropwise to solution 3, and continuing rapid stirring at room temperature to obtain solution 4, wherein the volume ratio of solution 3 to hydrogen peroxide solution is 12 mL:245 μL, and the mass volume concentration of hydrogen peroxide solution is 30%; (5) Centrifuging the milky blue solution 4 at 12000 rpm for 10 min to separate the solid product, and after washing, re-dispersing the product with deionized water to prepare a suspension of hyaluronic acid-modified calcium peroxide nanocomposite material with a concentration of 1 mg / mL; S2. Photosensitizer compounding (1) pll Preparation of Ce6: N-hydroxysuccinimide (NHS), N,N'-dicyclohexylcarbodiimide (DCC) and Ce6 were dissolved in a dry DMSO solution, and reacted at room temperature in the dark for 24 h to obtain Ce6-NHS, wherein the dosage ratio of NHS, DCC, Ce6 and DMSO was 3 mg:3 mg:1 mg:10 mL; N-ethylmorpholine (NEM), pll and Ce6-NHS were dissolved in dry DMSO, and reacted at room temperature in the dark for 24 h, and then dialyzed and freeze-dried to obtain the product. pll Ce6, the dosage ratio of NEM, pll, Ce6-NHS and DMSO is 1.2mg:01.2mg:7mg:10mL; (2) Add 1000 μL of 1 mg / mLpll Ce6 was added dropwise to 1200 μL of a suspension of hyaluronic acid-modified calcium peroxide nanocomposite material with a concentration of 1 mg / mL to obtain a mixed solution, which was placed on a rotary suspension instrument for 10 min; (3) The mixed solution was centrifuged at 12000 rpm for 10 min to separate the loaded pll Ce6 hyaluronic acid modified calcium peroxide nanoparticles.
[0058] Calculated pll In Ce6, the substitution degree of Ce6 on the pll chain is 5. After testing, the CaO2@HA / pll Ce6 zeta potential is +1.0 mV, and the surface is weakly positively charged, which can effectively penetrate into the biofilm. After initial penetration, a large amount of H2O2 is rapidly released in the weakly acidic and hyaluronidase (HAD) overexpressed bacterial biofilm microenvironment. CaO2@HA / pll The average particle size of Ce6 is 140 nm and it is evenly dispersed.
Claims
1. A composite drug-loaded nanoparticle based on a calcium peroxide carrier, characterized in that: Calcium peroxide nanoparticles modified with hyaluronic acid were used as carriers, and poly-lysine-dihydrochlorin e6 ( pll Composite drug-loaded nanoparticles CaO2@HA / pll Ce6, the composite drug-loaded nanoparticles are spherical particles with a particle size of about 100nm.
2. A method for preparing composite drug-loaded nanoparticles based on calcium peroxide carrier, comprising the preparation of hyaluronic acid-modified calcium peroxide nanomaterials and the compounding of effective ingredients, characterized in that: The active ingredient is compounded by poly-lysine-dihydrochlorin e6 ( pll Ce6) solution was added dropwise to the suspension of hyaluronic acid-modified calcium peroxide nanomaterials, and the solution was placed on a rotary suspension instrument for 10 min and centrifuged to obtain the loaded pll Ce6 modified calcium peroxide nanoparticles.
3. The method for preparing composite drug-loaded nanoparticles based on a calcium peroxide carrier according to claim 2, characterized in that: Said pll The concentration of Ce6 solution was 1 mg / mL, and the concentration of suspension of hyaluronic acid-modified calcium peroxide nanomaterials was 1 mg / mL.
4. The method for preparing composite drug-loaded nanoparticles based on a calcium peroxide carrier according to claim 2 or 3, characterized in that: Said pll The volume ratio of Ce6 solution and hyaluronic acid-modified calcium peroxide nanomaterial suspension is 1:1~1.
5.
5. A method for preparing composite drug-loaded nanoparticles based on a calcium peroxide carrier according to any one of claims 2 to 4, characterized in that: Poly-lysine-dihydrochlorin e6 ( pll Ce6) is prepared by dissolving N-hydroxysuccinimide (NHS), N,N'-dicyclohexylcarbodiimide (DCC) and Ce6 in a dry DMSO solution, reacting at room temperature in the dark for 24 h to obtain Ce6-NHS; N-ethylmorpholine (NEM), pll and Ce6-NHS are dissolved in dry DMSO, reacting at room temperature in the dark for 24 h, and then dialyzing and freeze-drying to obtain the product. pll Ce6.
6. The method for preparing composite drug-loaded nanoparticles based on a calcium peroxide carrier according to claim 5, characterized in that: The hyaluronic acid-modified calcium peroxide nanocomposite material is prepared according to the following steps: (1) Weigh sodium hyaluronate and hyaluronic acid, add them into deionized water, and sonicate to fully dissolve them to obtain solution 1; (2) Adding calcium chloride aqueous solution to solution 1, and rapidly stirring at room temperature to obtain solution 2; (3) Adding sodium hydroxide aqueous solution to solution 2 and mixing thoroughly to obtain solution 3; (4) adding hydrogen peroxide solution dropwise to solution 3 and continuing rapid stirring at room temperature to obtain solution 4; (5) The milky blue solution 4 was centrifuged at 12000 rpm for 10 min to separate the solid product. After washing, the product was re-dispersed with deionized water to prepare a suspension of hyaluronic acid-modified calcium peroxide nanocomposite material with a concentration of 1 mg / mL.
7. The method for preparing composite drug-loaded nanoparticles based on a calcium peroxide carrier according to claim 6, characterized in that: The dosage ratio of the sodium hyaluronate, hyaluronic acid and deionized water is 15-20 mg: 3-5 mg: 4-5 mL.
8. The composite drug-loaded nanoparticle based on calcium peroxide carrier according to claim 7, characterized in that: The volume ratio of the solution 1 to the sodium hydroxide aqueous solution is 2:0.8-1.2, and the concentration of the calcium chloride aqueous solution is 0.05-0.15 mol / L.
9. The method for preparing composite drug-carrying nanoparticles based on calcium peroxide carrier according to claim 8, characterized in that: The volume ratio of the solution 2 to the sodium hydroxide aqueous solution is 3:1.5-2.5, and the concentration of the sodium hydroxide aqueous solution is 2-3 mol / L.
10. The method for preparing composite drug-loaded nanoparticles based on a calcium peroxide carrier according to claim 9, characterized in that: The volume ratio of the solution 3 to the hydrogen peroxide solution is 12-13 mL: 240-250 μL, and the mass volume concentration of the hydrogen peroxide solution is 30%.
Citation Information
Patent Citations
Photodynamic combined lysozyme antibacterial method
CN112618716A
Ultrasonic sensitized nano-particles, application thereof and helicobacter pylori killing method
CN117257944A
Photodynamic and chemotherapy synergistic antibacterial composite material as well as preparation method and application thereof
CN119113109A
Polymer composite for helicobacter pylori recognition and composition for photodynamic therapy comprising same
US20210283257A1